Carbon fiber film-coated cloth and manufacturing method thereof
By bonding the thermoplastic coating layer on the surface of the carbon fiber fabric, combining pretreatment and gradient temperature-controlled heating, the problem of poor waterproofing performance of carbon fiber materials in humid environments is solved, and a carbon fiber coating cloth with high strength, good waterproofing performance and good binding force is achieved.
Patent Information
- Application Number
- CN202510313203.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-17
- Publication Date
- 2025-04-25
AI Technical Summary
Carbon fiber materials have poor waterproofing performance in humid environments, making it difficult to take into account high strength, good waterproofing performance and good binding force with carbon fiber.
The structure of the carbon fiber fabric layer and the two thermoplastic coating layers is adopted to optimize the bonding quality through pretreatment and gradient temperature-controlled heating, ensuring the tight fit between the coating and the carbon fiber fabric.
It significantly improves the waterproof performance and wear resistance of the carbon fiber laminated fabric, enhances the bonding strength between the coating and carbon fiber fabric, improves mechanical properties, and broadens the application range.
Smart Images

Figure CN119872015A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of carbon fiber, and in particular to a carbon fiber coated cloth and a manufacturing method thereof. Background Art
[0002] Carbon fiber is transformed from organic fiber through a series of heat treatment processes. Through these steps, non-carbon elements in the original fiber are removed, and the remaining structure is mainly carbon and forms an orderly arrangement, which gives carbon fiber its unique physical and mechanical properties. Carbon fiber is widely used in aerospace, automobile manufacturing, sports equipment, building reinforcement, electronic equipment and other fields due to its high specific strength, high modulus, corrosion resistance, high temperature resistance and other excellent properties.
[0003] However, carbon fiber materials have some obvious defects when used in daily life, which limit their wider application range. First of all, although carbon fiber materials have high strength and stiffness, due to the characteristics of their woven structure, they are easily affected by the external environment. The waterproof performance of the carbon fiber material itself is poor. Carbon fiber itself does not have good waterproof properties. When used in a humid environment or when it needs to contact liquids, it is easy to absorb water and cause performance degradation. The intrusion of water will also accelerate the aging of carbon fiber cloth and shorten its service life.
[0004] There have been some attempts on the market to improve the durability and waterproof performance of carbon fiber cloth by coating, impregnation or lamination. However, the shortcomings of the existing technology include that the existing carbon fiber cloth often finds it difficult to simultaneously take into account high strength, good waterproof performance and good bonding with carbon fiber.
[0005] Therefore, it is necessary to design a carbon fiber coated cloth and a manufacturing method thereof to solve the above problems. Summary of the invention
[0006] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a carbon fiber coated cloth and a manufacturing method thereof.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] A carbon fiber coated cloth comprises: a carbon fiber fabric layer woven from carbon fiber filaments; and two coating layers made of thermoplastic films, the two coating layers being respectively adhered and fixed to the two sides of the carbon fiber fabric layer.
[0009] As a preferred technical solution of the present invention, the diameter of the carbon fiber filaments is 5-10 um.
[0010] As a preferred technical solution of the present invention, the coating is made of one of plastic polyurethane, polyethylene terephthalate, polyetherimide, polyimide, polyvinyl chloride, and expanded polytetrafluoroethylene; the thickness of the coating is 0.01-5 mm.
[0011] A method for making a carbon fiber coated cloth comprises the following steps: S1: guiding the coated material into a heating machine for softening treatment; S2: preheating the adhesive; S3: applying the preheated adhesive on the surface of the coated film; S4: pasting the side of the coated film coated with the adhesive to the side of the carbon fiber fabric; S5: using a lightweight roller to perform preliminary compaction; S6: repeating steps S1-S5 to paste the coated film on the other side of the carbon fiber fabric to obtain a composite; S7: using a flat heater to compact the composite after preliminary compaction again; S8: naturally cooling the composite to room temperature, and performing operations such as winding and cutting off waste materials, to finally obtain the carbon fiber coated cloth.
[0012] As a preferred technical solution of the present invention, before step S1, the carbon fiber fabric layer is pretreated, and the pretreatment includes: A1: cleaning with a mild organic solvent that will not affect the performance of the sizing agent on the carbon fiber precursor; A2: drying the cleaned carbon fiber fabric layer; A3: plasma treating the cleaned and dried carbon fiber braid; A4: preheating the treated carbon fiber braid.
[0013] As a preferred technical solution of the present invention, in step A4, the preheating temperature is 60-80°C.
[0014] As a preferred technical solution of the present invention, the adhesive is one of silicone, thermoplastic polyurethane, acrylic acid and polyamide.
[0015] As a preferred technical solution of the present invention, in step S2, the adhesive after preheating is placed in a vacuum device for degassing, the vacuum degree is set to 0.5-1 bar, and the vacuum state is maintained for 5-10 minutes.
[0016] As a preferred technical solution of the present invention, in step S3, the film coated with the adhesive is placed on an ultrasonic vibration table for vibration, with a vibration frequency of 20-100 Hz and a vibration time of 10-20 s.
[0017] As a preferred technical solution of the present invention, the operating environment temperature of steps S3-S7 is 40-60°C.
[0018] The present invention has the following beneficial effects:
[0019] 1. Enhanced waterproof performance: This application enhances the tightness of the connection between the carbon fiber fabric surface by bonding the film on the surface and effectively treating it, ensuring that the adhesive can be evenly distributed and firmly attached, reducing the possibility of water penetration and improving the waterproof performance of the film-coated fabric;
[0020] 2. Significantly improved wear resistance: The bonding quality is optimized through gradient temperature control heating, preheating of adhesive, vacuum degassing and ultrasonic vibration, ensuring that the adhesive is evenly distributed and tightly fitted, reducing the gaps and bubbles at the interface, improving the stability and durability of the overall structure, thereby enhancing the wear resistance. The initial compaction by lightweight rollers and the secondary compaction by flat heaters ensure that the coating is tightly fitted on the carbon fiber fabric, eliminating air bubbles and other defects, and further enhancing the wear resistance.
[0021] 3. Optimized mechanical properties: Through plasma treatment, carbon fiber fabric preheating treatment and gradient temperature controlled heating, the peel strength between the coating and the carbon fiber fabric is significantly improved, ensuring that the product will not easily delaminate or peel off when subjected to force. This high peel strength also improves the shear strength and tensile strength, allowing the product to exhibit better mechanical properties in complex environments, thereby effectively broadening the application range of the product and improving its applicability and reliability. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a schematic structural diagram of a carbon fiber coated cloth proposed by the present invention;
[0023] Figure 2 is a flow chart of pretreatment of carbon fiber fabric;
[0024] Figure 3 The figure is a flow chart for the preparation of carbon fiber coated cloth. DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0026] Reference Figure 1-3 A carbon fiber coated cloth comprises a carbon fiber fabric layer and two coating layers, wherein the carbon fiber fabric layer is woven from carbon fiber yarns, the coating layer is made of a thermoplastic waterproof film, and the two coating layers are fixed on the two sides of the carbon fiber fabric layer by gluing.
[0027] When weaving, select carbon fiber precursors of the same and appropriate size, usually with a diameter of 5-10um. Use a precision tension controller to set the appropriate initial tension for the fiber precursors before weaving to ensure that they remain consistent throughout the weaving process.
[0028] Furthermore, the carbon fiber braid needs to be pretreated before performing step S1, and the pretreatment includes:
[0029] A1: Use a mild organic solvent such as isopropyl alcohol that will not affect the performance of the sizing agent on the carbon fiber precursor. Specifically, use an ultrasonic cleaner to clean the carbon fiber braid. Place the braid in an ultrasonic cleaning tank with a frequency of 30-50kHz and a power density of 0.5-1W / cm 2 The cleaning time is 5-10 minutes, which can remove dust, oil and other impurities that may be contaminated during the weaving process, providing a clean foundation for subsequent surface modification. The cavitation effect produced by ultrasonic vibration can completely remove tiny particles and pollutants in hard-to-reach areas, ensuring the cleaning effect;
[0030] A2: Dry the cleaned carbon fiber fabric using a hot air oven at a drying temperature of 60-80°C for 10-30 minutes;
[0031] A3: Plasma treatment is performed on the cleaned and dried carbon fiber braid to increase the surface energy of the fabric, introduce new functional groups, and enhance the chemical adhesion between the braid and the coating material. A low-temperature plasma treatment machine is used to lay the braid flat on the placement table, start the vacuum pump, set a low vacuum environment of about 0.1-1Pa, and a power of 100-200W. Oxygen is introduced into the treatment chamber. The treatment time is 40-60s. The distance between the electrode and the fabric is 5-10mm. The other side of the braid is plasma treated in the same way.
[0032] A4: Preheat the treated carbon fiber braid at a temperature of 60-80°C. Preheating can reduce the viscosity of the adhesive or coating material, making it easier to penetrate between the fibers of the braid, forming a more uniform bonding layer, reducing air entrainment between the braid and the adhesive, and reducing the probability of bubble and void formation, thereby improving the bonding quality.
[0033] Furthermore, the method for making the carbon fiber coated cloth is as follows, wherein the carbon fiber fabric used is pretreated by the above method:
[0034] S1: guiding the coating material into a heating machine for softening treatment, wherein the coating has a thickness of 0.1-2 mm, and the coating is made of one of plastic polyurethane, polyethylene terephthalate, polyetherimide, polyimide, polyvinyl chloride, and expanded polytetrafluoroethylene. Specifically, a heating plate is used to soften the coating, and the heating temperature is 60-100° C. to prevent the coating from being overheated, damaged, or adhered;
[0035] Secondly, the coating needs to be cleaned with deionized water and dried before softening to prevent impurities on the coating from affecting the subsequent bonding effect.
[0036] Furthermore, during the softening process, the coating is heated by gradient temperature control, with a temperature change rate of 2-8°C / min, 1-3min for each gradient, and 3-5min at the highest heating temperature. This can reduce the thermal stress inside the coating and prevent cracks or other defects caused by rapid heating. Secondly, it ensures that all parts of the coating are heated evenly, enhancing the bonding effect and the stability of the overall structure.
[0037] S2: preheating the adhesive, which is one of silicone, thermoplastic polyurethane, acrylic acid and polyamide. Specifically, pouring the adhesive into a heating container, stirring with a stirrer while heating, wherein the preheating temperature is 40-60°C, the preheating time is 10-30 minutes, and the stirrer speed is 100-300 rpm. The preheating operation can reduce the viscosity of the adhesive, making it easier to flow, ensuring that it can fully fill the tiny gaps and uneven surfaces on the coating and carbon fiber fabric, thereby enhancing the bonding effect;
[0038] Furthermore, the adhesive that has been stirred and preheated is placed in the vacuum chamber of the vacuum equipment, and the vacuum pump is slowly turned on to gradually reduce the pressure. The vacuum degree is set to 0.5-1 bar, and the vacuum state is maintained for 5-10 minutes to allow the bubbles to fully escape. Then, the atmospheric pressure is slowly restored to avoid bonding defects caused by bubbles, ensure close contact at the interface, and improve bonding quality and durability.
[0039] S3: evenly apply the preheated adhesive on the surface of the film, further, place the film on an ultrasonic vibration table, apply the adhesive and start the device to allow the film and the adhesive to vibrate, and then use high-frequency vibration to improve the fluidity and flatness of the adhesive, wherein the vibration frequency is 20-100 Hz, the vibration time is 10-20s, and the overall operating environment is maintained at 40-60°C. Ultrasonic vibration can generate high-frequency vibration and cavitation effect, so that the adhesive is more evenly distributed on the film;
[0040] S4: Place the adhesive-coated side of the film on the carbon fiber fabric, and keep the operating environment temperature at around 40-60°C. This helps the adhesive maintain fluidity and promotes initial bonding. It is worth noting that the area of the film should be larger than the area of the carbon fiber fabric, which can reduce the alignment accuracy and operation difficulty when the two are bonded together, and secondly prevent the subsequent compaction operation from causing deviation between the positions of the two.
[0041] S5: Use a lightweight roller to perform preliminary compaction on the material. Starting from one end of the film, slowly and evenly roll the roller in one direction. This can help expel the air from under the film and make the film fit tightly on the carbon fiber fabric. The weight of the roller is 1-3kg to provide appropriate pressure without damaging the material. The rolling speed is 30-60cm / min, and the number of rolling times is 1-3 times. Each rolling must be ensured to move in the same direction to prevent the introduction of new bubbles. The operating environment is still at 40-60℃;
[0042] S6: Repeat steps 1-5 to adhere the coating to the other side of the carbon fiber fabric;
[0043] S7: Use a flat plate heater to compact the material after preliminary compaction again. Specifically, use the pressure system of the flat plate heater or an external hydraulic / pneumatic device to apply uniform pressure to the assembly to ensure uniform pressure distribution and avoid local overpressure causing material deformation. The temperature of the flat plate heater is set between 60-80°C, the compaction time is 3-10min, and the applied pressure is 0.5-3Mpa. Furthermore, the flat plate heater adopts a gradient temperature change method with a temperature change rate of 2-5°C / min and a stay time of 2-5min per gradient. This can reduce the thermal stress inside the coating, carbon fiber fabric and adhesive, and prevent cracks or delamination during the cooling process, thereby improving the bonding strength and durability.
[0044] S8: The composition is naturally cooled to room temperature, and operations such as winding and cutting off waste are performed to finally obtain a carbon fiber coated cloth.
[0045] Furthermore, a hydrophobic coating is applied on the surface of the finished carbon fiber coated cloth. The hydrophobic layer can effectively prevent moisture from penetrating into the interior of the coated cloth. Secondly, it can resist ultraviolet radiation, temperature changes and chemical corrosion, thereby extending the service life of the product, reducing aging and fading, and is suitable for application outdoors and in harsh environments.
[0046] Example 1
[0047] Select carbon fiber precursor with a diameter of 8um, put the precursor on a braiding machine and weave it to obtain a carbon fiber braid;
[0048] The carbon fiber braid was pretreated and cleaned using an ultrasonic cleaner with a frequency of 40 kHz and a power density of 0.8 W / cm 2The cleaning time is 8 minutes, and then it is dried using a drying device. The drying temperature is 70°C and the time is 20 minutes. The braided fabric is plasma treated using a low-temperature plasma processor. The vacuum degree is 0.5Pa, the power is 150W, oxygen is introduced, the treatment time is 50s, and the distance between the electrode and the fabric is 8mm. The other side is plasma treated in the same way. Finally, the carbon fiber braid is preheated at 70°C for 20 minutes.
[0049] The preparation steps of carbon fiber coated cloth are as follows:
[0050] S1: A plastic polyurethane coating material with a thickness of 0.5 mm is guided into a heating machine to soften, and the heating temperature is 60°C;
[0051] S2: preheating the silicone adhesive at a temperature of 50°C for 20 minutes and a stirring speed of 200 rpm, placing the adhesive after stirring and preheating into a vacuum chamber of a vacuum device, setting the vacuum degree to 0.8 bar, and maintaining the vacuum state for 5 minutes;
[0052] S3: Apply the preheated adhesive evenly on the surface of the film;
[0053] S4: The adhesive-coated side of the film is attached to the carbon fiber fabric, and the operating environment temperature is maintained at about 50°C;
[0054] S5: Use a light roller to roll slowly and evenly in one direction from one end of the film at a speed of 40 cm / min;
[0055] S6: Repeat steps 1-5 to adhere the coating to the other side of the carbon fiber fabric;
[0056] S7: Use a flat plate heater to compact the material after preliminary compaction again, the temperature is set between 70°C, the compaction time is 5 minutes, and the applied pressure is 1Mpa;
[0057] S8: The composition is naturally cooled to room temperature, and operations such as winding and cutting off waste are performed to finally obtain a carbon fiber coated cloth.
[0058] Example 2
[0059] Different from Example 1, in step S3, an ultrasonic vibrator is used to vibrate the adhesive and the film, the vibration frequency is 50 Hz, the vibration time is 10 s, and the overall operating environment is maintained at 50° C. The rest is the same as Example 1.
[0060] Example 3
[0061] Different from Example 1, in step S1, the coating is heated and softened by gradient temperature control, the temperature change rate is 5°C / min, each gradient stays for 2 minutes, and the highest temperature stays for 3 minutes. The rest is the same as Example 1.
[0062] Example 4
[0063] The difference from Example 1 is that in step S1, the thickness of the plastic polyurethane coating material is 1 mm, and the rest is the same as Example 1.
[0064] Comparative Example 1
[0065] The difference from Example 1 is that the carbon fiber braid is not pretreated, and the other aspects are the same as Example 1.
[0066] Comparative Example 2
[0067] The difference from Example 1 is that in step S1, the coating is not softened. The other steps are the same as Example 1.
[0068] Comparative Example 3
[0069] The difference from Example 1 is that the adhesive is not preheated, and the other aspects are the same as Example 1.
[0070] Comparative Example 4
[0071] Different from Example 1, in steps S5-S7, a coating coated with adhesive is covered on one side of the carbon fiber fabric and compacted using a flat heater, then the composition is turned over, another coating coated with adhesive is covered on the other side of the carbon fiber fabric, and compacted again, the temperature is set between 70°C, the compaction time is 5 minutes, and the applied pressure is 1 MPa.
[0072] Comparative Example 5
[0073] Different from Example 1, in step S1, the thickness of the plastic polyurethane coating material is 7 mm.
[0074] The above embodiments and comparative examples were subjected to the following performance tests:
[0075] 1. Waterproofness. Referring to GB / T 4744-2013 "Testing and evaluating the waterproof performance of textiles - Hydrostatic pressure method", a circular sample with a diameter of 100 mm was cut from the carbon fiber coated cloth to be tested. At least 5 parallel samples were prepared for each embodiment and comparative example to ensure the reliability of the data. The samples were placed under standard atmospheric conditions at a temperature of 20°C ± 2°C and a relative humidity of 65% ± 5% for at least 4 hours to ensure that the test conditions were consistent. A hydrostatic pressure tester was used at a test rate of 1 kPa / min. The measurement results are as follows:
[0076]
[0077] According to the above table, by comparing Examples 1-3 and Comparative Examples 1-3, Examples 1-3 perform better in terms of waterproof performance, wherein Example 2 further optimizes the distribution of the adhesive by introducing an ultrasonic vibrator, thereby obtaining a higher hydrostatic pressure value. For Comparative Examples 1-4, the waterproof performance is significantly reduced, especially Comparative Example 2, which does not undergo a coating softening treatment, seriously affecting the bonding effect between the coating and the carbon fiber fabric, resulting in the lowest hydrostatic pressure value. Compared with Example 1, Examples 4 and Comparative Example 5 both improve the waterproof performance by increasing the coating thickness.
[0078] 2. Abrasion resistance: Referring to GB / T 21306-2007 “Determination of wear resistance of textiles - Flat abrasion method”, a circular sample with a diameter of 38 mm was cut from the carbon fiber coated cloth to be tested. At least 5 parallel samples were prepared for each embodiment and comparative example. The samples were placed under standard atmospheric conditions at a temperature of 20°C ± 2°C and a relative humidity of 65% ± 5% for at least 4 hours. The samples were tested using a Martindale abrasion tester. The number of cycles from the start of the test to the first rupture point or obvious wear of the sample was recorded. The measurement results are as follows:
[0079]
[0080] It can be seen from the above experimental data that Examples 1-3 are superior to Comparative Examples 1-3 in terms of wear resistance, wherein Example 2 further optimizes the distribution of the adhesive by introducing an ultrasonic vibrator, thereby obtaining excellent wear resistance, and Example 4 and Comparative Example 5 improve the wear resistance by increasing the thickness of the coating. The wear resistance of Comparative Examples 1-3 is significantly reduced, especially Comparative Example 2, which does not perform a coating softening treatment, seriously affects the bonding effect between the coating and the carbon fiber fabric, resulting in the lowest wear resistance.
[0081] 3. Peel strength: Refer to GB / T 2792-2014 "Test method for 180° peel strength of pressure-sensitive adhesive tape". Cut the carbon fiber coated cloth to be tested into strip samples with a width of 25 mm and a length of 200 mm. Prepare at least 5 parallel samples for each embodiment and comparative example. Place the samples under standard atmospheric conditions at a temperature of 20°C ± 2°C and a relative humidity of 65% ± 5% for at least 4 hours. The measurement results are as follows:
[0082]
[0083]
[0084] It can be seen from the table that the peel strength between the coating and the carbon fiber woven layer in Examples 1-3 is better than that in Comparative Examples 1-3 as a whole, especially in Comparative Example 2, where no coating softening treatment is performed, which seriously affects the bonding effect between the coating and the carbon fiber fabric, resulting in the lowest peel strength. In Example 4, the thickness of the coating is increased, and the peel strength is enhanced, while the increase in thickness in Comparative Example 5 reduces the peel strength. This is because although the bonding area is the same, an excessively thick coating introduces additional stress concentration points, which may affect the uniform distribution of the adhesive and reduce the flexibility of the material, making it more likely to crack or delaminate when subjected to stress.
[0085] In summary, the carbon fiber coated cloth proposed in the present application improves the waterproofness and wear resistance of the carbon fiber coated cloth by improving the uniformity and fit of the adhesive between the coating and the carbon fiber layer, softening the coating, and performing special treatment on the carbon fiber woven fabric. At the same time, it improves the bonding strength between the coating and the carbon fiber fabric, thereby improving the mechanical properties of the carbon fiber coated cloth as a whole, so that the coated cloth has a wider range of application scenarios and better economic benefits.
[0086] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A carbon fiber coated cloth, characterized in that: include: A carbon fiber fabric layer, woven from carbon fiber filaments; Two coating layers are made of thermoplastic films and are respectively adhered and fixed on two sides of the carbon fiber fabric layer.
2. The carbon fiber coated cloth according to claim 1, characterized in that: The diameter of the carbon fiber filament is 5-10um.
3. The carbon fiber coated cloth according to claim 1, characterized in that: The coating is made of one of plastic polyurethane, polyethylene terephthalate, polyetherimide, polyimide, polyvinyl chloride, and expanded polytetrafluoroethylene; The thickness of the coating is 0.01-5 mm.
4. A method for producing a carbon fiber coated cloth, characterized in that: The following steps are involved: S1: guiding the coating material into a heating machine for softening; S2: preheating the adhesive; S3: Apply the preheated adhesive to the lamination surface; S4: Lay the adhesive-coated side of the covering film onto one side of the carbon fiber fabric; S5: Initial compaction using lightweight rollers; S6: Repeat steps S1-S5 to adhere a film to the other side of the carbon fiber fabric to obtain a composite; S7: using a flat heater to compact the initially compacted composition again; S8: The composition is naturally cooled to room temperature, and operations such as winding and cutting off waste are performed to finally obtain a carbon fiber coated cloth.
5. The method for manufacturing a carbon fiber coated cloth according to claim 4, characterized in that: Before step S1, the carbon fiber fabric layer is pretreated, and the pretreatment includes: A1: Use a mild organic solvent that will not affect the performance of the sizing agent on the carbon fiber precursor; A2: Drying the cleaned carbon fiber fabric layer; A3: Plasma treatment of the cleaned and dried carbon fiber braid; A4: Preheat the treated carbon fiber braid.
6. The method for manufacturing a carbon fiber coated cloth according to claim 4, characterized in that: In the step A4, the preheating temperature is 60-80°C.
7. The method for manufacturing a carbon fiber coated cloth according to claim 4, characterized in that: The adhesive is one of silicone, thermoplastic polyurethane, acrylic and polyamide.
8. The method for manufacturing a carbon fiber coated cloth according to claim 4, characterized in that: In the step S2, the adhesive after preheating is placed in a vacuum device for degassing, the vacuum degree is set to 0.5-1 bar, and the vacuum state is maintained for 5-10 minutes.
9. The method for manufacturing a carbon fiber coated cloth according to claim 4, characterized in that: In the step S3, the film coated with the adhesive is placed on an ultrasonic vibration table for vibration, with a vibration frequency of 20-100 Hz and a vibration time of 10-20 seconds.
10. A carbon fiber coated cloth and a method for making the same according to claim 9, characterized in that: The operating environment temperature of steps S3-S7 is 40-60°C.
Citation Information
Patent Citations
Carbon fiber and metal plate gluing process based on ultrasonic vibration assistance
CN106926472A
Carbon fiber fabric self-lubricating gasket material, and preparation method and application thereof
CN111269663A
Carbon fiber film-coated cloth and manufacturing method thereof
CN112829391A
Binder spraying metal 3D printing powder forming density regulating and controlling device
CN117798383A